Practices of strength and conditioning coaches in Brazilian elite soccer - Loturco, I.; Freitas, T. T.; Alcaraz, P. E.; Kobal, R.; Hartmann Nunes, R. F.; Weldon, A.; Pereira, L. A. (Biology of Sport, 2022)
Brazil is the leading global exporter of soccer players, with approximately 2,000 international transfers to different clubs per year. Although Brazilian players compete in the most prestigious soccer leagues worldwide, the habitual training methods, strategies, and routines of Brazilian soccer strength and conditioning coaches (SCCs) are undocumented. This study used a standard online survey to collect and characterize the strength and conditioning practices of Brazilian soccer SCCs. Forty-nine SCCs (age: 40.4 ± 7.5 years; professional experience: 15.3 ± 7.5 years) working in Brazilian professional soccer teams participated in this study. The survey consisted of eight sections: 1) background information; 2) muscular strength-power development; 3) speed training; 4) plyometrics; 5) flexibility training; 6) physical testing; 7) technology use; and 8) programing. Results indicated that training and testing practices of Brazilian SCCs are strongly affected by the congested fixture schedules, extensive traveling distances, and socio-economic disparities between different regions of the country. We describe all these different strategies and methods in detail, providing a comprehensive view and a critical examination of Brazilian soccer strength and conditioning practices. Brazilian SCCs and professional soccer organizations can use the findings from this study to develop training strategies and customize education programs. Practitioners from other countries can use this information to design training programs closely tailored to the background of Brazilian athletes, which may support their adaptation to different competitive scenarios and game demands, such as those found in the most important soccer leagues worldwide.